Maximum power point tracking control scheme for small scale wind turbine - Badawi, Ahmed Samir Abed
The electric energy crisis has emerged as a significant global problem in the last decade. Therefore, many governments put an ambitious goal to supply a significant portion of their electrical grid from renewable energy such as wind energy. The generation, distribution and transmission of electricity in Palestine have recently emerged as major issues, In Palestine there is a deficit in electricity due to siege and prevailing war-torn conditions. Moreover, due to limited area the typical types of electricity generation are not feasible to satisfy the demand. Hence small scale wind turbine approach is introduced. The current MPPT algorithms are not suitable for Palestine due to different wind speed condition. The main aim of this research is to achieve maximum power point tracking for small scale wind turbine. Improved algorithm has been proposed to increase the efficiency of the wind energy conversion system (WECS). The new algorithm enhanced the three mode algorithm to solve the tradeoff between efficiency and convergence speed. This study analysed data using seven numerical methods to check the wind energy feasibility for Palestine. There are two approaches employed: analysis of two sets of actual time series data and theoretical Weibull probability function. In this analysis, the parameters Weibull shape factor 'k' and the Weibull scale factor 'c' were adopted. The performance of these numerical methods was tested by five statistical tools to check efficiency performance. Graphical Method (GM) and energy pattern factor (EPF) show the greatest efficiency, whereas the second modified maximum likelihood method (SMMLM) show the low efficiency based on statistical tools. Based on numerical analysis shape factor is approximately 2. Therefore, the probability distribution function (PDF) for Palestine is Weibull. Whereas Scale factor value from 4-5 m/s. The total wind power for 2012, 2013, 2014 and 2015 are 977, 744, 808 and 1084 W (per unit area), respectively. Thus, this study confirms the potential of electrical energy generation in Palestine using small-scale turbines based on wind power density (WPD) calculations. The proposed algorithm shows fast tracking capability and enhanced stability under change wind speed conditions using Matlab/Simulink. The theoretical results confirm that the proposed improved algorithm